Low abundance of floating marine debris in the northern Baltic Sea - Rothäusler Eva; Jormalainen Veijo; Gutow Lars; Thiel Martin (Elsevier Ltd, 2022)
We determined the spatial and seasonal distribution of Floating Marine Debris (FMD) by visual ship surveys across the northern Baltic Sea between Finland and Sweden. FMD density was comparatively low, and we found the highest debris density close to major port cities. The seasonal variation in debris density was not pronounced although we observed more FMD items during the summer surveys. Plastic bags were the most common identifiable litter items, and we also found other consumer items (plastic bottles and cups). Styrofoam items suggest fishing or aquaculture activities as potential sea-based sources of FMD. These are the first data on FMD density in the Baltic Sea, and they are substantially lower than those reported for other coastal waters, which may be due to (i) lower human population densities, and (ii) higher environmental awareness in the Scandinavian countries.